PERBEDAAN KARAKTERISTIK KELUARGA DENGAN KEJADIAN GIZI KURANG PADA BALITA SUKU BAJO DAN NON BAJO DI WILAYAH PESISIR KOTA KENDARI - Irma, Irma; Masluhiya AF, Swaidatul (Universitas Tribhuwana Tunggadewi, 2020)
Malnutrition is a problem that occurs globally, especially in developing countries, including Indonesia. Malnutrition in todllers influenced by various factors such as socio-economic factors, sanitation, behavior and infectious diseases. The purpose of this study to know differences family characteristics (family income, mother's knowledge and parenting) with the incidence of malnutrition in the Bajo and non-Bajo tribe toddlers. This research is a quantitative type study with a comparative design, with a population of all Bajo and non-Bajo tribe toddlers who experience malnutrition in the coastal area of Kendari City. A sample of 82 people were taken with the Simple Random Sampling technique and the mother of toddlers as respondents. The research instrument used was a questionnaire. Furthermore, the data collected has been analyzed statistically by the Independent Sample t Test. The results of this study indicate that there is a significant difference between maternal knowledge and parenting with the incidence of malnutrition in Bajo and non-Bajo tribe toddlers and there is no difference in family income with the incidence of malnutrition in Bajo and non-Bajo tribal toddlers.